CHARACTERISTICS SEDIMENT IN THE ULAKAN TAPAKIS WATER OF PADANG PARIAMAN DISTRICT WEST SUMATERA PROVINCE - Fertikasari, Indah; Rifardi, Rifardi; Elizal, Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbtracThe study of the distribution of sedimentary characteristics in Ulakan Tapakis waters aimed at sediment deposition environmental conditions based on sedimentary characteristics. Sediment sampling was conducted at nine sampling points using purposive sampling technique.Analysis of the sediment fraction was carried out using the wet sieveand pipette methods. The results of the study the Ulakan Tapakis waters had 4 types of sediment namely: sand, muddy sand, sandy mud and mud,which is dominated by sandy mud. The sedimentary statistical parameters showed the value of mean diameter (mean size) range from 0,23-5,73ø with the clasification of coarse sand to medium silt. Skewness values range from -0,90-0,42ø with the clasification of very negative skewed to very positive skewed. The values of sorting ranges from 2,04-2,53ø with the clasification of very poorly sorted. The value of kurtosis range from 0,47-9,31ø with the clasification of very platikurtik to leptokurtik extreme, indicate the waters under the influence of current conditions that tend to be unstable and the number of anthropogenic aktivities. Keyword: Sedimentary Characteristics, Sediment statistics, Ulakan Tapakis